The Hindu personality in education : Tagore, Gandhi, Aurobindo - Cenkner, William, 1930- (Manohar Book Service, 1976)
On the role of Rabindra Nath Tagore, 1861-1941, Mohandas Karamchand Gandhi, 1869-1948, Aurobindo Ghose, 1872-1950 as religious personalities in the development of an educational philosophy and praxis.